(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
This article examines the phenomena of monopoly and monopsony, two important forms of market structure, from an economic theory perspective. It analyzes the essence of monopoly, its causes, types, and pricing strategies. It also examines the concept of monopsony and its role in the economy, as well as its impact on producers and consumers. The article presents ideas on limiting competition in a monopolistic market, pricing, and the need for government regulation.